Characterization of Tattoo Aftercare Products: Allergenic Ingredients and Marketing Claims. Issue 5 (September 2021) - Liou, Yujie Linda; Liszewski, Walter; Schlarbaum, Jamie P.; Warshaw, Erin M.
Abstract : Background: Common recommendations for tattoo aftercare to ensure proper healing include application of topical products. Little is known about tattoo aftercare products. Methods: Tattoo aftercare products were identified from a previous study and a search on Amazon.com using the phrase "tattoo aftercare." Duplicates and products without complete ingredient lists were excluded. Marketing claims were tabulated. All ingredients were entered in Excel and grouped according to Contact Allergen Management Program categories. Comparison of ingredients to North American Contact Dermatitis Group (NACDG) screening and American Contact Dermatitis Society (ACDS) Core allergens was conducted. Results: A total of 84 tattoo aftercare products from 52 distinct brands were found. Forty-eight distinctive market claims were identified; the use of "natural ingredient(s)" (42.9%) was most common. There were 4 to 28 ingredients per product (mean = 11.8 ± 5.5) with a total of 369 distinct ingredients listed. Products contained an average of 7.9 ± 3.9 ACDS Core allergens per product and 7.0 ± 3.7 NACDG allergens per product. Most common allergens included fragrance/botanicals (n = 529), vitamin E derivatives (n = 43), and vitamin B5 derivatives (n = 11). Conclusions: This review of 84 products found that tattoo aftercare products contain an average of 8 ACDS Core and 7 NACDG allergens. Clinicians should be aware of potential allergens in tattoo aftercare products.